2018
DOI: 10.1016/j.placenta.2017.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the cardiovascular circulation in fetuses of mothers with diabetes: A fetal computational model analysis

Abstract: Blood flow is redistributed in FMDM to the placenta, away from the brain. This alteration may play a role in the postnatal health of these fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Models that impose a prescribed pressure or flow profile obtain this profile either by a simple function [e.g., ( 80 , 82 , 92 )] or from patient data [e.g., ( 74 , 76 )]. When using patient data, the prescribed pressure or flow profile could be used to find parametric differences between healthy and pathological cases by fitting the suspected influenced parameters to the prescribed profile ( 75 77 ). In addition, a patient-specific model can be obtained when using measured blood velocity profiles ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Models that impose a prescribed pressure or flow profile obtain this profile either by a simple function [e.g., ( 80 , 82 , 92 )] or from patient data [e.g., ( 74 , 76 )]. When using patient data, the prescribed pressure or flow profile could be used to find parametric differences between healthy and pathological cases by fitting the suspected influenced parameters to the prescribed profile ( 75 77 ). In addition, a patient-specific model can be obtained when using measured blood velocity profiles ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…The parameters of this model are first tuned to mimic healthy fetuses and subsequently verified on fetuses with fetal growth restriction ( 75 , 76 ). In addition, this model has been used to evaluate the differences of fetal hemodynamics from diabetic and non-diabetic mothers ( 77 ).…”
Section: Fetal Circulatory Modelsmentioning
confidence: 99%
“…Several of this mechanism have been postulated and include fetal growth restriction, preeclampsia, preterm birth, assist reproductive technology (ART), exposure to toxic drugs, twin-to-twin transfusion syndrome (TTTS) and maternal diabetes and obesity. Evidence suggests that ART induces alterations in cardiac and vascular morphology and physiology ( 2 5 ). In this collection, Li et al , conducted a comprehensive review of epigenetic mechanisms associated with an increased risk of cardiovascular disease (CVD) in offspring conceived via ART.…”
Section: Fetal Cardiovascular Remodeling and Post-natal Cardiac Functionmentioning
confidence: 99%
“…These findings highlighted an essential mechanism of fetal circulatory adaption in IUGR patients. Similarly, the ultrasound-derived LPNs of fetuses whose mothers had diabetes mellitus (FMDMs) showed that placental resistance and cerebral artery diameters significantly decreased, while cerebral vascular resistance and aortic diameter significantly increased [ 136 ] when compared to healthy fetuses, with differences exacerbated by increased gestational stage. The morphological and hemodynamic changes uncovered through the LPN correlate with enhanced placental flow and reduced cerebral flow, suggesting a mechanism for why FMDMs tend to have an enlarged placenta and underdeveloped brain.…”
Section: Lumped Parameter Models Of Fetal Circulationmentioning
confidence: 99%
“…The validation of fetal hemodynamic simulation results is key to their accuracy and reliability. As with pediatric and adult simulations, fetal simulation results are typically validated using in vitro or in vivo (Doppler) measurements and comparisons [ 133 , 134 , 135 , 136 , 141 , 142 , 170 ]. While Doppler measurements are excellent for reduced-order model validation, 3D simulations may benefit from more extensive spatial validation.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%